A Cooperative Approach for Topology Control in Wireless Sensor Networks: Experimental and Simulation Analysis - Costa, Paolo; Cesana, Matteo; Brambilla, Stefano; Casartelli, Luca; Pizziniaco, Luca (The 9th IEEE International Symposium on a World of Wireless, Mobile and Multimedia Networks (WOWMOM'08), Newport Beach, CA, USA, June 2008., 2008)
The choice of the transmission power levels adopted in Wireless Sensor Networks (WSNs) is critical to determine the performance of the network itself in terms of energy efficiency, connectivity and spatial reuse, since it has direct impact on the physical network topology. In this paper, a cooperative, lightweight and fully distributed approach is introduced to adaptively tune the transmission power of sensors in order to match local connectivity constraints. To accurately evaluate the topology control solution, a small-scale testbed based on MicaZ sensor nodes is deployed in indoor and outdoor scenarios. Practical measures on local connectivity, multi-hop connectivity, convergence time and emitted power are used to compare the proposed approach against previously proposed ones. Moreover, a simulation analysis complements the experimental one in large-scale WSN scenarios, where a testbed implementation becomes unfeasible.